Pembuatan Sistem Akuisisi Data Sederhana Menggunakan Arduino-Python (Studi Kasus: Suhu Fluida Pada Tangki Pemanas) - Dita Nurhalimah; Muhammad Iwan Fermi; Zulfansyah Zulfansyah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Data acquisition (DAQ) is a part of control system and almost applied in all aspects, in industrial automation processes. The main objective of this research is to construct the DAQ using Arduino Python-based in developing a graphical user interface (GUI). The system consists of two components, i.e. hardware and software, which are designed on client-runtime module. PyQt5 was chosen as the basis for developing the GUI. The DAQ system testing is carried out on a stirred heating tank with the observations of fluid temperatures and actuation element is electric heaters. The GUI allows users to be able to visualize and store data in real time mode. The performance of the system is verified based on manual observation. It was found that the system could be carried out for interactive manual control. Even so, the created system can be used for data collection process in the process control laboratory in Chemical Engineering Department of Riau University. In the future, it is expected that the performance of the system can be improved.Keywords: data acquisition, control, Arduino, Python, GUI